The Culture of Volunteer Work among University Students - Ibrahim, Suhad Tahseen; Musa, Wathiq Omar (Journal of Tikrit University for Humanities, 2025)
The current research aims to identify the level of the culture of volunteer work among University Students. Differences in the Culture of volunteer work for university students according to the variables of gender (male-female), specialization (scientific-humanities), and academic year (first -furth). In order to achieve the objectives of the research, the researcher has prepared a scale for (the culture of Volunteer work), which consists of 35 paragraphs and each paragraph offering 5 response alternatives are: (Strongly agree ,Agree, Don’t know, Disagree, strongly Disagree). The researcher extracted the psychometric properties for the scale of the culture of volunteer work, for distinction and validity in its logical and structural logical types. As for persistence, it was extracted using (test-retest method and Cronbach's Alpha coefficient).The researcher has applied the scale to the research sample, which was tested using a stratified random method consists of (400) male and female students, from the first and furth academic grade from the University of Kirkuk from morning studies, divided equally into (200) students from scientific faculties and (200) students from humanities faculties. The statistical methods used in the research including (Chi-square test, Pearson correlation coefficient, Cronbach's Alpha equation, one-sample and two-sample t-tests, and three-way analysis of variance). After processing the data statistically using the SPSS statistical package, The results of the research showed that: the students have a high level of volunteer work culture. There were statistically significant differences according to the gender variable (male-female) in favor of females. There were no statistically significant differences according to the specialization (scientific-humanities) or the academic stage (first-furth) grade. In light of the research results, the researcher came up with several recommendations and suggestions.